INTEGRASI PROGRAM MARKETING DAN PUBLIC RELATIONS UNTUK MEMENANGKAN PERSAINGAN - Melita, Yerah (Jurnal Insani, 2014)
Marketing Public Relations (MPR) is a new marketing concept or discipline which emerged in the 1990s. The concept of MPR appears to complement and fill the roles of both marketing and public relations that are expected to be more successful marketing purposes.Integration efforts between marketing and public relations can improve credibility (trust) of the messages conveyed through the public relations so that it can penetrate the situation relatively difficult to reach by advertising.Integration of ,marketing and public relations will also improve the efficiency and effectiveness so that the MPR is able to compete and win the competition.